2023
DOI: 10.3390/ijerph20021139
|View full text |Cite
|
Sign up to set email alerts
|

Comment on Naranjo-Bonilla et al. Retinal and Choroidal Effects of Continuous Positive Airway Pressure as Treatment for Sleep Apnea: Results at 12 Months. Int. J. Environ. Res. Public Health 2022, 19, 12637

Abstract: We read with great interest the article by Naranjo-Bonilla et al. concerning changes in retinal and choroidal thickness (ChT) in patients with obstructive sleep apnea (OSA) who underwent continuous positive airway pressure treatment (CPAP) [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Furthermore, correlations are independent from age and AL, factors that could introduce a bias in the analysis of correlation [34]. In terms of ChT, we failed to detect any difference between the two groups.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, correlations are independent from age and AL, factors that could introduce a bias in the analysis of correlation [34]. In terms of ChT, we failed to detect any difference between the two groups.…”
Section: Discussionmentioning
confidence: 55%
“…We are aware that this may limit the information on the morphologic correlation to other eye structures. 32…”
Section: Resultsmentioning
confidence: 99%
“…We are aware that this may limit the information on the morphologic correlation to other eye structures. 32 secondary adhesions between the RPE and the retina prevent proper healing; thus, applying subretinal BSS around the fovea might solve this problem. 21 Reis et al showed improvement of BCVA with complete closure of stage IV macular holes using a perifoveal incision technique after a previous failed closure in 7 patients 28 : five perifoveal retinal incisions were done radial as deep as the RPE near the borders of the hole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation